The comparison of treatment with clobetasol propionate 0.05% and topical pimecrolimus 1% treatment in the treatment of alopecia areata - Ucak, Haydar; Kandi, Basak; Cicek, Demet; Halisdemir, Nurhan; Dertlioglu, Selma Bakar (Informa Healthcare, 2012)
Background: Alopecia areata (AA) is a non-scarring hair loss. Objective: We aimed the comparison of clobetasol propionate and pimecrolimus efficiency and tolerability in the treatment of AA. Methods: The study included a total of 100 consecutive patients with AA. Patients were randomized into four groups. 30 patients used 1% pimecrolimus cream, 30 patients used 0.05% clobetasol propionate cream, 20 patients used petrolatum as placebo. Scalp of 20 patients was divided into two equal areas and one area was treated with 1% pimecrolimus cream and the other area with 0.05% clobetasol propionate cream. Results: At week 12 of treatment, the recovery rate of the pimecrolimus group was 53.73 +/- 44.49 and the recovery score was 3.63 +/- 2.07; that of the clobetasol propionate group was 47.00 +/- 44.80 and the recovery score was 3.33 +/- 2.20; that of the placebo group was 35.50 +/- 40.53 and the recovery score was 2.75 +/- 1.88. There was no statistically significant difference among the groups in terms of the percentage of recovery and the recovery score (p < 0.05). Conclusion: In conclusion, we detected that topical pimecrolimus treatment is as effective as topical corticosteroids and is superior to topical corticosteroids in terms of side effects in the treatment of AA.
Keywords: alopecia areata; clobetasol propionate; pimecrolimus